EVALUASI PENGELOLAAN PROGRAM PENGEMBANGAN USAHA AGRIBISNIS PERDESAAN (PUAP) DI KABUPATEN SIGI (Studi Pada Gapoktan Sigampa Desa Kaleke Kecamatan Dolo Barat) - Subaedah, Subaedah (Katalogis, 2017)
This study is aimed to: 1) describe the implementation of rural agribusiness development program in Sigi; 2) determine and analyze constraints in rural agribusiness development program in Sigi; 3) provide alternative solution to management policy of rural agribusiness development program. Method of study is descriptive qualitative. The key informant is a farmer supervisor and second informant is the head of BP4K of Sigi Regency. Data collecting methods include observation, interview, and documentation. Technique of data analysis uses data triangulation. The results conclude that: 1) the management of rural agribusiness development program in terms of the input side shows that the vision, missions, objectives, and distribution mechanism in Gapoktan Sigampa (Farmers’ Association) in Sigi Regency has met the rules of PEDUM PUAP, yet still not optimal in terms of management. From the output side, it shows that Gapoktan empowerment and increase in revenue is not optimal. In terms of outcome, agribusiness micro-financial institution as the target of rural agribusiness development program has not yet formed; 2) problems identified include: a) trust, in the formation of micro finance institution, b) programs not synergized, c) lack of understanding and awareness of farmers about being independent, d) lack of entrepreneurial creativity, e) the effort in managing the group is not optimal; 3) the results of rural agribusiness development program are not physically visible but based on farmers’ independency that is resulted from their empowerment; this can increase their welfare. The result cannot be seen from the economic indicators in a short time but based on the participation and self-reliance of farmers on an ongoing basis. Sustainability management in Sigampa farmer’s association covers the following: a) developing capital model in rural micro-financial program, b) strengthening organizational culture: increase awareness of empowerment, c) organizational trust: build social relationship in micro-finance institution, and d) organizational design: strategy to establish the agribusiness micro-finance institution.